TINGKAT KESUKAAN ANAK USIA DINI TERHADAP COOKIES WORTEL DITINJAU DARI UJI ORGANOLEPTIK - Maria M Lawe Bai; Yunus Karyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early childhood is a phase of rapid growth and development that requires balanced nutritional intake, yet picky eater behavior often leads to low vegetable consumption, including carrots, which are rich in beta-carotene, vitamin A, fiber, and antioxidants. One effort to increase children's vegetable consumption is through food product innovation in the form of carrot cookies. This study aims to determine the level of preference of early childhood children toward carrot cookies based on organoleptic parameters of color, aroma, taste, and texture. This study used a quantitative approach with a one-shot case study design and an organoleptic test using a facial-expression-based hedonic scale. The sample consisted of four formulations, namely P0 (0%), P10 (10%), P20 (20%), and P30 (30%) carrot substitution, with 42 children aged 5-6 years as untrained panelists. Data were analyzed descriptively, including mean, minimum, maximum, and standard deviation values. The results showed that early childhood children's preference for carrot cookies fell into the like to very like category across all organoleptic parameters, with the highest mean value found in formulation P0 and the lowest in P30. Although there was a tendency for mean values to decrease as the percentage of carrot addition increased, all formulations remained within a good acceptance category, indicating that carrot cookies have potential as a healthy vegetable-based snack alternative that remains acceptable to early childhood children.